A new method for microplastic sampling and isolation in mountain glaciers: A case study of one antisana glacier, Ecuadorian Andes - Cabrera, Marcela (2020)
Microplastic contamination has become ubiquitous in terrestrial and marine environments. Recent studies have shown that the wind can transport and deposit microplastics in high mountain ecosystems, but microplastic contamination therein is unknown. Because mountain glaciers are the primary source of drinking water for large urban areas in the Andes, assessing recent and historical microplastic contamination is crucial. Surface snow can indicate recent microplastic deposition, whereas glacial ice cores can provide information on historical contamination. At mountain glaciers, the inhospitable conditions and the difficult accessibility are limiting factors for sampling. Therefore, sampling and laboratory analytical methods have to be integrated and planned ensuring replicability. Here, we present 1) a new methodology to identify sampling areas within the accumulation zone of a glacier to obtain samples of surface snow and ice cores; 2) a less-manipulative analytical technique for the preparation and isolation of microplastics derived from glaciers. In addition, we identified the minimum amount of sample necessary to obtain robust data on contamination by microplastics.